Graphite from sustainable sources and methods of making same
By preparing graphite materials with excellent performance through coking, calcining and graphitization from renewable and sustainable resources without using catalysts, the problem of low graphite preparation efficiency in the prior art is solved, and efficient graphite preparation and lithium-ion battery performance improvement are achieved.
Patent Information
- Application Number
- CN202380065539.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-18
- Filing Date
- 2023-08-17
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to efficiently prepare graphite materials from renewable, recyclable or sustainable resources, especially without the use of coking, calcining or graphitization catalysts.
By providing a raw material containing at least one aromatic compound, coking, calcining and graphitization, the specific steps include coking in the range of 300°C to 650°C, calcining in the range of 900°C to 1500°C, and graphitizing in the range of 2200°C to 3200°C, without using a catalyst throughout the process.
A catalyst-free graphitization method is achieved from renewable and sustainable resources, and graphite materials with excellent performance are prepared, anode materials suitable for lithium-ion batteries, showing high charging capacity and first cycle coulomb efficiency.
Smart Images

Figure CN119894821A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Application No. 63 / 399,047, filed on August 18, 2022, the entire contents of which are incorporated by reference into this application. Background Art
[0003] The demand for lithium-ion battery materials is expected to increase significantly over the next decade, primarily due to the expected increase in demand for electric vehicles. Meeting this demand will require not only scaling up current methods of generating materials, but also developing new methods of generating these materials.
[0004] Graphite is the most common anode material in lithium-ion batteries. There are two types of graphite: synthetic graphite and natural graphite. Traditionally, synthetic graphite is produced by graphitizing petroleum coke, while natural graphite is mined using various processes and then purified. There is a need in the art for methods that can efficiently prepare graphite from renewable, recyclable or sustainable resources. Summary of the invention
[0005] Most carbonaceous materials treated at high temperatures but without a catalyst will only carbonize to form disordered amorphous carbon materials or ordered soft carbon materials with crosslinked domains, or ordered soft carbon materials with graphite domains. See Sagues et al., "A simple method for producing bio-based anode materials for lithium-ion batteries", Green Chem., 2020, 22, 7093. The inventors have surprisingly discovered a method for graphitizing raw materials derived from renewable and sustainable raw materials without the use of coking, calcining or graphitization catalysts.
[0006] One embodiment of a non-catalytic graphitization method comprises (a) providing a feedstock comprising at least one aromatic compound, the feedstock derived from a sustainable or renewable source; (b) coking the feedstock at a temperature in a range of 300°C to 650°C to provide coke; (c) calcining the coke at a temperature in a range of 900°C to 1500°C to provide calcined coke; and (d) graphitizing the calcined coke at a temperature in a range of 2200°C to 3200°C.
[0007] Also described is graphite prepared by the disclosed non-catalytic graphitization method. Also described is graphite independent of the disclosed graphitization method, characterized by a spacing of 002 planes (d 002 ) ranges from 0.335nm to 0.338nm, and the grain size in the c-axis direction (L c ) ranges from 20nm to 45nm.
[0008] Also described are lithium-ion batteries having an anode comprising graphite prepared by the disclosed graphitization method, or regardless of how the material is graphitized, and a cathode and an electrolyte disposed between the anode and the cathode. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] The foregoing summary of the invention and the following detailed description of the present disclosure may be better understood when read in conjunction with the accompanying drawings. For the purpose of illustrating the present disclosure, the accompanying drawings show some but not all alternative embodiments. The present disclosure is not limited to the precise arrangements and means shown. The following drawings, which are incorporated into and constitute a part of the specification, help explain the principles of the present disclosure.
[0010] Figure 1 A diagram illustrating a graphitization process starting from a feedstock that is a residue of a biomass pyrolysis process is shown.
[0011] Figure 2 Shown is an overlaid powder x-ray diffraction pattern of biographite compared with the pattern of Birla Carbon's synthetic graphite BCG18.
[0012] Figure 3 A photograph of one embodiment of ground and powdered bio-graphite prepared according to the disclosed method is shown.
[0013] Figure 4 A particle size distribution graph of one embodiment of biographite is shown.
[0014] Figure 5 Shown are electrochemical data obtained from a cell utilizing bio-graphite as part of the anode material.
[0015] Figure 6 is a plot of voltage versus specific capacity, which shows that biographite exhibits the expected lithium intercalation chemistry of typical graphite. See, for example, Allart et al., "Model of Lithium Intercalation into Graphite by Potentiometric Analysis with Equilibrium and Entropy Change Curves of Graphite Electrode", Journal of the Electrochemical Society, 165(2) A380-A387 (2018).
[0016] Figure 7Electrochemical data of NMC532 full cells (coin cells) constructed with bio-graphite are shown.
[0017] Figure 8 Additional data collected from NMC532 bio-graphite full-cell coin cells are shown, which show impressive rate performance, including 70.8% capacity retention at 2 °C.
[0018] Fig. 9 is a graph showing the results of additional electrochemical testing of a NMC811 full cell, which shows a first cycle coulombic efficiency of 78.5%. The right side of the graph shows a cell using a reference non-biological graphite. DETAILED DESCRIPTION
[0019] In one aspect, a method of producing graphite comprises providing a feedstock comprising at least one aromatic compound, the feedstock derived from a sustainable or renewable source; coking the feedstock at a temperature in the range of 300° C. to 650° C. to provide coke; calcining the coke at a temperature in the range of 900° C. to 1500° C. to provide calcined coke; and graphitizing the calcined coke at a temperature in the range of 2200° C. to 3200° C. The process in some aspects does not involve the use of any catalyst in any part of the process, including in the calcining and graphitizing steps.
[0020] "Sustainable or renewable source" refers to a resource that can be continued or renewed, e.g., naturally or otherwise replenished, recycled, etc., so that the source is not eventually completely exhausted. Examples include biomass, oils derived from biomass, man-made materials such as plastics, etc.
[0021] In one aspect, the coking step can be carried out at a temperature ranging from 300°C to 650°C to provide coke. In another aspect, the coking step can be carried out at a temperature ranging from 400°C to 600°C. In another aspect, the coking step can be carried out at a temperature ranging from 450°C to 500°C. In another aspect, the coking step can be carried out at a temperature of about 500°C. When the term "about" appears before a numerical value here and elsewhere in the present application, the value can vary by plus or minus 10% unless otherwise stated. In a specific aspect, the coking step can be carried out at a temperature of about 500°C for about five hours in an inert atmosphere such as nitrogen. As discussed above, the coking step can be carried out without any catalyst (including an aromatization catalyst).
[0022] The coke can be calcined at a temperature generally ranging from 900° C. to 1500° C. to provide a calcined coke. In one aspect, the coke can be calcined at a temperature ranging from 1000° C. to 1400° C. In another aspect, the coke can be calcined at a temperature ranging from 1100° C. to 1300° C. In another aspect, the coke can be calcined at a temperature of about 1200° C., for example in a furnace of an inert gas such as nitrogen. As discussed above, the calcining step can be performed in the absence of any catalyst, including an aromatization catalyst.
[0023] The calcined coke can generally be graphitized at a temperature in the range of 2200° C. to 3200° C. In one aspect, the calcined coke can be graphitized at a temperature in the range of 2300° C. to 3100° C. In another aspect, the calcined coke can be graphitized at a temperature in the range of 2400° C. to 3000° C. In another aspect, the calcined coke can be graphitized at a temperature in the range of 2500° C. to 2900° C. In another aspect, the calcined coke can be graphitized at a temperature in the range of 2600° C. to 2800° C. In another aspect, the calcined coke can be graphitized at a temperature of about 2700° C., for example, in a furnace under an inert atmosphere such as helium.
[0024] On the one hand, the feedstock comprises residual oil remaining from a process comprising the following steps: pyrolyzing biomass to recover at least one of benzene, toluene or xylene from an aromatization fraction of the pyrolyzed biomass. Oil or bio-oil can be obtained on the one hand by producing a vapor fraction of hydrocarbons from a biomass feed stream in the presence of a cracking catalyst. The vapor fraction can be separated from other oxygen-containing organic compounds and a cracking catalyst, and the vapor fraction can then be converted into a product comprising aromatic compounds, for example using an aromatization catalyst such as a zeolite catalyst. The desired aromatic compounds can then be removed, leaving a bio-oil residue. This bio-oil residue can be used as a feedstock for the disclosed graphitization method in some aspects. Although the feedstock can be pyrolyzed or aromatized with a catalyst, it should be understood that embodiments of the method for graphitizing the feedstock do not involve the use of any catalyst.
[0025] Biomass pyrolysis processes for the preparation and recovery of aromatic compounds, specifically benzene, toluene, and xylenes, are further described in U.S. Patent Publication No. 2017 / 0247617A1 to Schenk et al. A similar plastic pyrolysis process for the preparation of similar aromatic compounds is also described in U.S. Patent Publication No. 2022 / 0195310A1 to Schenk et al. Both the '617 and '310 patent disclosures are incorporated herein by reference in their entirety as they teach pyrolysis processes that leave bio-oil or other residues suitable for use as a sustainable or renewable feedstock for the disclosed graphitization process.
[0026] As will be further understood by reference to the '617 application, in some aspects, the biomass used in the pyrolysis process can be lignocellulosic biomass, such as plants or wood, including softwoods such as pine. In other aspects, the biomass used in the pyrolysis process can comprise agricultural waste, plants, wood, or a combination thereof.
[0027] The inventors surprisingly found that the bio-oil derived from the bio-oil remaining residue of the above-mentioned biomass pyrolysis process has a certain degree of aromaticity and aromaticity, so no catalyst (e.g., an aromatization catalyst) is required to further aromatize the bio-oil feedstock or otherwise catalyze the calcination or graphitization step. In some aspects, the at least one aromatic compound in the feedstock constituting at least 60% by weight of the feedstock, for example, at least 65% by weight, at least 70% by weight, at least 75% by weight, at least 80% by weight, at least about 85% by weight, at least about 90% by weight, or at least 95% by weight or more of the feedstock is one or more aromatic compounds.
[0028] On the one hand, the raw material comprises at least one of the following: xylene, toluene, o-xylene, trimethylbenzene, benzene, naphthalene, ethylbenzene or indene. In other aspects, the raw material comprises one or more of xylene, toluene or benzene. In still other aspects, the raw material comprises xylene, toluene and benzene. On the other hand, the raw material comprises at least one of the following: xylene, toluene, o-xylene, trimethylbenzene, benzene, naphthalene, ethylbenzene or indene, wherein xylene is present in the raw material in an amount of at most 80% by weight of the raw material, toluene is present in the raw material in an amount of at most 80% by weight of the raw material, o-xylene is present in the raw material in an amount of at most 25% by weight of the raw material, trimethylbenzene is present in the raw material in an amount of at most 25% by weight of the raw material, benzene is present in the raw material in an amount of at most 80% by weight of the raw material, naphthalene is present in the raw material in an amount of at most 25% by weight of the raw material, ethylbenzene is present in the raw material in an amount of at most 25% by weight of the raw material, and indene is present in the raw material in an amount of at most 5% by weight of the raw material. The raw material can also include other aromatic or non-aromatic compounds. In one aspect, the feedstock is a liquid or oil at 25°C.
[0029] In one aspect, the feedstock contains no anthracene. In another aspect, the feedstock contains no methylated anthracene. In another aspect, the feedstock contains no aromatic oxygenated products. In another aspect, the coke prepared from the feedstock contains no anthracene. In another aspect, the coke prepared from the feedstock contains no methylated anthracene. In another aspect, the coke prepared from the feedstock contains no aromatic oxygenated products. In another aspect, the calcined coke contains no anthracene. In another aspect, the calcined coke contains no methylated anthracene. In another aspect, the calcined coke contains no aromatic oxygenated products. In some aspects, these aromatic materials can be formed by conventional graphitization processes using certain aromatization catalysts.
[0030] Also disclosed is graphite prepared by any of the disclosed methods. In one aspect, the graphite is "biographite," which refers to graphite derived from biological carbon such as biomass. In one aspect, the graphite prepared by the graphitization method is characterized by a spacing between the interlayer distances (d 002 ) ranges from 0.335nm to 0.338nm, and the grain size in the c-axis direction (L c ) is in the range of 20 nm to 45 nm. In another aspect, the charge capacity of the graphite prepared by the graphitization method is greater than 315 mAh / g, such as greater than 320 mAh / g, greater than 325 mAh / g or greater than 330 mAh / g.
[0031] Also disclosed is a lithium ion battery (LiB) having an anode comprising graphite prepared by the disclosed graphitization method, a cathode, and an electrolyte disposed between the anode and the cathode. In one aspect, the electrolyte comprises a vinylene carbonate additive. In another aspect, the LiB is capable of achieving a first cycle coulombic efficiency of at least 90% at a charge capacity of greater than 330 mAh / g.
[0032] Also disclosed is a graphite derived from a sustainable or renewable raw material, independent of the disclosed graphitization method, wherein the graphite is characterized by an interlayer spacing (d 002 ) ranges from 0.335nm to 0.338nm, and the grain size in the c-axis direction (L c ) ranges from 20 nm to 45 nm. In one aspect, the graphite has a charge capacity greater than 315 mAh / g. In another aspect, the graphite is derived from biomass. In another aspect, the graphite is derived from lignocellulosic biomass. Also disclosed are lithium ion batteries (LiBs) having an anode, and a cathode and an electrolyte disposed between the anode and the cathode, the anode comprising graphite derived from a sustainable or renewable raw material and having an interlayer distance and a grain size of the c-axis. In one aspect, the electrolyte comprises a vinylene carbonate additive.
[0033] A. Example
[0034] The following examples further illustrate the present disclosure. The scope of the present disclosure and claims is not limited by the scope of the following examples.
[0035] The residual oil from the biomass pyrolysis process, which is a liquid oil at room temperature and includes a mixture of aromatic compounds including one or more of the following: xylene, toluene, o-xylene, trimethylbenzene, benzene, naphthalene, ethylbenzene and indene, was first coked in a tube furnace in a ceramic boat under nitrogen at 500°C for five hours. The resulting coke was calcined in a furnace at 1200°C under nitrogen. The calcined coke was graphitized in a furnace at 2700°C under helium to produce bio-graphite.
[0036] Graphitization of coke is Figure 1 The X-ray diffraction data shown in Table 1 show the yields of calcination and graphitization. (002) d spacing and L c The data are shown in Table 2, with reference to synthetic graphite BCG18 produced by Birla Carbon (Marietta, GA, USA).
[0037] Table 1
[0038] step Starting mass (g) End mass (g) Yield (%) Coking -- 18.6 -- Calcination 18.6 17.3 93.0 Graphitization 17.3 17.2 99.4
[0039] Table 2
[0040] characteristic unit Biocoke Bio-calcined coke Bio-graphite BCG18 (002)d-spacing nm 0.3455 0.3471 0.3370 0.3365 <![CDATA[L c ]]> nm 2.6 2.6 28.9 41.4
[0041] and Figure 2 The pattern of Bola BCG18 shown in Figure 1 is compared to the powder X-ray diffraction pattern of bio-graphite. Figure 3 A photo of the ground and powdered bio-graphite is shown in Figure 1. The particle size of the bio-graphite is similar to that of typical battery-grade graphite. The particle size distribution is shown in Figure 2. Figure 4 Table 3 shows the particle size distribution data in addition to the specific capacity and first cycle coulombic efficiency data achieved with the bio-graphite in the electrochemical half-cell.
[0042] Table 3
[0043] characteristic unit Bio-graphite <![CDATA[D V 10]]> μm 7.6 <![CDATA[D V 50]]> μm 13.1 <![CDATA[D V 90]]> μm 22.5 1st cycle discharge capacity mAh / g 332 First cycle Coulombic efficiency % 90.3
[0044] As shown in Table 3, the bio-graphite from biomass pyrolysis residue achieved a capacity of 332 mAh / g and a first-cycle Coulombic efficiency of 90.3%. Figure 5Additional electrochemical data are shown in . In comparison, biographite prepared using catalytic graphitization had a specific capacity of 335 mAh / g, but a first cycle Coulombic efficiency of only 68.5%. Biographite produced using carbon coating catalysis increased the first cycle Coulombic efficiency to 87.9%, but reduced the specific capacity to 301 mAg / g. The relatively low first cycle Coulombic efficiency of the uncoated biographite is most likely due to the relatively small particle size to which the material was ground. This property is significantly improved by increasing the particle size using a carbon coating, but can alternatively be achieved by optimizing the grinding parameters, where graphite reaches 10-20 micron DV without a carbon coating. 50 Carbon coating is primarily intended to improve conductivity, although an increase in particle size may also provide benefits in Coulombic efficiency. In general, specific capacity should also increase with increasing graphitization temperature of biocalcined coke. The degree of graphitization and specific capacity are directly related.
[0045] like Figure 6 As shown, biographites prepared according to embodiments of the disclosed methods exhibit the expected lithium intercalation chemistry of graphites typically used in lithium batteries.
[0046] NMC532 full cells (coin cells) were constructed with bio-graphite, and electrochemical data from these cells are shown in Figure 7 As shown. Figure 8 As shown, the NMC532 bio-graphite full-cell coin cell exhibits impressive rate performance, including 70.8% capacity retention at 2 °C. Fig. 9 As shown, additional electrochemical testing showed that bio-graphite has excellent performance as an anode material. It is believed that the performance of bio-graphite as an anode material can be further improved by using an electrolyte containing vinylene carbonate as an additive.
[0047] The features and advantages of the present disclosure are apparent from the detailed description, and the claims cover all such features and advantages. For those skilled in the art, there will be many changes, and any changes equivalent to those described in the present disclosure fall within the scope of the present disclosure. It will be appreciated by those skilled in the art that the concepts upon which the present disclosure is based can be used as a basis for the design of other methods and systems for performing the several purposes of the present disclosure. Therefore, the claims should not be considered to be limited by the description or examples.
Claims
1. A method for producing graphite, the method comprising: a) providing a feedstock comprising at least one aromatic compound, said feedstock being derived from a sustainable or renewable source; b) coking the feedstock at a temperature ranging from 300° C. to 650° C. to provide coke; c) calcining the coke at a temperature ranging from 900° C. to 1500° C. to provide calcined coke; as well as d) graphitizing the calcined coke at a temperature ranging from 2200° C. to 3200° C.; The method described therein does not involve the use of a calcined or graphitized catalyst.
2. The method of claim 1, wherein the feedstock comprises residual oil remaining from a process comprising the step of pyrolyzing biomass to recover at least one of benzene, toluene or xylenes from an aromatized fraction thereof.
3. The method of claim 2, wherein the biomass is lignocellulosic biomass.
4. The method of claim 2 or 3, wherein the biomass comprises agricultural waste, plants, wood or a combination thereof.
5. The process according to any one of the preceding claims, wherein the feedstock is free of anthracene.
6. The process according to any one of the preceding claims, wherein the feedstock is free of methylated anthracene.
7. The process according to any one of the preceding claims, wherein the feedstock is free of aromatic oxygenated products.
8. The process according to any one of the preceding claims, wherein the at least one aromatic compound constitutes at least 60% by weight of the feedstock.
9. The process of any one of the preceding claims, wherein the feedstock comprises at least one of the following: xylenes, toluene, o-xylene, trimethylbenzene, benzene, naphthalene, ethylbenzene, or indene.
10. A process according to any one of the preceding claims, wherein the feedstock is a liquid or an oil at 25°C.
11. Graphite prepared by a method according to any one of the preceding claims. 12 . A lithium-ion battery (LiB) having an anode comprising the graphite according to claim 1 , a cathode and an electrolyte arranged between the anode and the cathode.
13. The battery of claim 12, wherein the electrolyte comprises a vinylene carbonate additive.
14. A graphite derived from a sustainable or renewable raw material, the graphite being characterized by a 002 plane interlayer spacing (d 002 ) ranges from 0.335nm to 0.338nm, and the grain size in the c-axis direction (L c ) ranges from 20nm to 45nm.
15. The graphite according to claim 14, having a charge capacity greater than 315 mAh / g.
16. Graphite according to claim 14 or 15, which is derived from biomass.
17. Graphite according to claim 16, derived from lignocellulosic biomass.
18. A lithium ion battery (LiB) having an anode comprising the graphite according to any one of claims 14 to 17, a cathode and an electrolyte disposed between the anode and the cathode.
19. The battery of claim 18, wherein the electrolyte comprises a vinylene carbonate additive.
Citation Information
Patent Citations
Process for the Preparation of Aromatic Compounds
US20170247617A1
Process for the preparation of low molecular weight aromatic compounds such as benzene, toluene, and xylenes (BTX) from plastics
US20220195310A1